COMPUTERIZED SYSTEM ADMINISTRATIVE DATA PROCESSING AND NEW STUDENT LPBM CIKUPA TANGERANG - Idi Candra; Irfan. Skom. MM Irfan. Skom. MM (Jurnal Sistem Informasi, 2002)
Computer technology develops very quickly, with this development had much of acompany which uses a computerized system in data processing employees.Computerized system is very helpful way of working of an institution in processingstudent data when compared to manual systems. For that purpose in writing thisresearch, the author wants to give input at the institution during the course how tosolve this problem is to convert the manual system to computerized system.Given this input operation authors hope this course will more quickly and efficiently